2020
DOI: 10.1021/acs.est.0c00351
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Environmentally Persistent Free Radicals on Total Particulate Matter Collected from Electronic and Tobacco Cigarettes

Abstract: In the current study, electron paramagnetic resonance (EPR) spectroscopy was employed to measure environmentally persistent free radicals (EPFRs) in the total particulate matter (TPM) of mainstream and sidestream TPM of conventional cigarettes and the TPM of ecigarettes. Comparable concentrations of EPFRs were detected in both sidestream (8.05 ± 1.32) × 10 4 pmol/g and mainstream TPM (7.41 ± 0.85) × 10 4 pmol/g of conventional cigarettes. TPM exposure to air resulted in long-lived oxygen centered, secondary ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 66 publications
3
24
0
Order By: Relevance
“…4 and Table S3). These samples showed an initial slight increase in EPFRs after the first year, possibly due to the formation of secondary radicals during oxidative aging as previously described for pyrolysis of tobacco 38 . Over the subsequent four sampling years, the EPFR concentrations decreased only slightly, with the most pronounced reduction occurring in the fifth year (Fig.…”
Section: Epfr Abundance Depends On Carbonizationsupporting
confidence: 73%
“…4 and Table S3). These samples showed an initial slight increase in EPFRs after the first year, possibly due to the formation of secondary radicals during oxidative aging as previously described for pyrolysis of tobacco 38 . Over the subsequent four sampling years, the EPFR concentrations decreased only slightly, with the most pronounced reduction occurring in the fifth year (Fig.…”
Section: Epfr Abundance Depends On Carbonizationsupporting
confidence: 73%
“…Shein et al [89] observed similar amounts of free radicals in aerosols using standard wicking and heating, a mesh coil, and an air control. Hasan et al [90] found free radical concentration from two closed-system ENDS were significantly lower than conventional tobacco cigarettes, but the oxidative potency from the free radicals originating from the ENDS was much higher. No clear relationship between free radicals and device design has been observed.…”
Section: Ros and Free Radicalsmentioning
confidence: 99%
“…Group A HPLC 41 [14, 22-26, 28, 30-33, 36-38, 40, 41, 45-48, 60-65, 67, 69, 70, 74-76, 79, 80, 82-84, 97, 106, 110, 111, 114] 3 [47,50,69] GC-FID 3 [39,68,92] 2 [39,71] TD-GC-MS 2 [94,95] 4 [50,64,94,95] GC-MS 11 [29, 33, 34, 39, 41-43, 69, 81, 93, 105] 13 [39,48,49,51,59,69,76,79,83,85,93,105,114] 7 [49,59,69,76,83,85,114] EPR 8 [14,56,58,73,84,[88][89][90] ICP-MS 11 [49, 52-54, 60, 69, 78, 79, 83, 86, 114] ICP-OES 4 [51,87,112,113] SF-ICP...…”
Section: Carbonyls Vocs a Trace Elements Ros And Free Radicals Pahs Tmentioning
confidence: 99%
“…Many organic molecules are EPFR precursors. These classes of organic compounds have been reported to form EPFRs: aromatics [40,43,44] chloroaromatics [2,[45][46][47][48], polycyclic aromatic hydrocarbons (PAHs) [49,50], complex organic polymers [31,51], and microplastics [52]. Another abundant source of EPFR precursors is soil, which contains a vast reservoir of metals and organics [20].…”
Section: Sources and Precursors Of Epfrsmentioning
confidence: 99%